Potential Habitats of Siamese Crocodiles and False Gharials in East Kalimantan for Conflict Resolution - Larasati, Firda; Setiawan, Yudi; Kusrini, Mirza Dikari (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Concerns in crocodiles sustainability have long been overlooked, due to humans fear of its ferocity and unresolved human-crocodile conflicts. The siamese crocodile (Crocodylus siamensis) and false gharial (Tomistoma schlegelii) are considered threatened by the IUCN red list because of their limited range and declining populations. In this study we developed habitat suitability model for both species and overlaid with anthropogenic factors to mitigate conflict between crocodiles and human in Mesangat-Suwi Wetland, East Kalimantan, Indonesia. We collected species presence from 2018–2023, measured environmental variables, interviewed 100 respondents, and mapped all information with Maximum Enthropy program (MaxEnt). Results showed that different factors influenced the habitat distribution for each species. Specifically, distance from swamps was affected the most for both crocodiles. Our model found that the potential habitat was much smaller than the non-potential ones due to humans’ intrusion. Much of the Mesangat-Suwi area was covered in high-conflict zones between humans and crocodiles, endangering both species even more. Hence, serious actions were urgently needed to resolve the conflict, either by prevention and mitigation actions, to ensure human-crocodile coexistence in East Kalimantan.